Detection of activated perforasome patterns and the correlation with acute internal load parameters during and following incremental cycling - Masur, L.; Willenbockel, H. F.; Cordes, T.; Sperlich, B.; Düking, P. (European Journal of Applied Physiology, 2025)
Purpose Infrared thermography can be used to investigate the kinetics of thermoregulatory processes during exercise. The kinetics of the thermal contrast index (TCI), associated with activated perforasomes, and correlation with selected cardiovascular, metabolic, and subjective parameters have not been investigated during exercise.